Analysis of organic intermediates with a low-load Pd/Al2O3 catalyst for the ethanol-SCR of NO at low temperatures: The influential role of NH3 and catalyst characterization. (15th October 2021) - Chen, Hanyu; Lou, Wei; Sun, Sirui; Wang, Xi
Highlights: The organic intermediates of ethanol-SCR and (ethanol + NH3 )-SCR were identified by SVUV-PIMS. The main reaction pathways of ethanol-SCR over Pd/Al2 O3 were summarized. The ammonia and temperature dependence of the reaction mechanism were investigated. XRD, XPS, SEM and EDS of the fresh and used catalysts were performed. Abstract: To effectively remove the NOx produced in diesel exhaust, ethanol-SCR over a Pd/Al2 O3 catalyst was studied by synchrotron vacuum ultraviolet photoionization mass spectrometry combined with photoelectric ionization efficiency spectroscopy. The effects of NH3 and temperature on the catalytic oxidation of ethanol to produce intermediates were postulated under normal atmospheric pressure. Moreover, the catalyst phase composition was verified by XRD, XPS, SEM and EDS characterization, and the active surface changes due to the addition of NH3 were investigated. The results show that the catalytic oxidation path of ethanol included ethylene, acetaldehyde and acetic acid regardless of NH3 addition, but organic intermediates such as nitromethane and acetonitrile significantly decreased or disappeared after NH3 addition. With increasing temperature, the types of organic intermediates first increased and then decreased, and most intermediates were adopted at 250 °C. Acetic acid formation over a Pd/Al2 O3 catalyst had a subtle relationship with temperature and NH3 .